2016
DOI: 10.1073/pnas.1516110113
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MIR165/166 by class II and class III homeodomain leucine zipper proteins establishes leaf polarity

Abstract: A defining feature of plant leaves is their flattened shape. This shape depends on an antagonism between the genes that specify adaxial (top) and abaxial (bottom) tissue identity; however, the molecular nature of this antagonism remains poorly understood. Class III homeodomain leucine zipper (HD-ZIP) transcription factors are key mediators in the regulation of adaxial-abaxial patterning. Their expression is restricted adaxially during early development by the abaxially expressed microRNA (MIR)165/166, yet the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 31 publications
4
85
0
Order By: Relevance
“…Unfortunately, multiple loss-of-function HD-Zip II mutants are difficult to test in shade, since they are strongly altered in embryo, SAM activity, leaf polarity, gynoecium and fruit development under simulated sunlight conditions [121,136,138], implying a fundamental role of these proteins in the regulation of plant growth and development. Indeed, there are evidences that alteration of selected HD-Zip II proteins affects at least a regulatory circuit between HD-Zip II and HD-Zip III transcription factors [111,117,121,136,155] and hormones signal transduction pathways [139,180].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, multiple loss-of-function HD-Zip II mutants are difficult to test in shade, since they are strongly altered in embryo, SAM activity, leaf polarity, gynoecium and fruit development under simulated sunlight conditions [121,136,138], implying a fundamental role of these proteins in the regulation of plant growth and development. Indeed, there are evidences that alteration of selected HD-Zip II proteins affects at least a regulatory circuit between HD-Zip II and HD-Zip III transcription factors [111,117,121,136,155] and hormones signal transduction pathways [139,180].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that HD-Zip II proteins work as repressors of gene expression [27,121,123], it was proposed that, among other possibilities, they may negatively regulate molecules that restrict HD-Zip III expression [112]. Interestingly, it was recently shown that REV, whose expression is restricted to the adaxial side of the leaf through the activity of miR165/166, physically interacts with HAT3 and ATHB4 to directly repress MIR165/166 expression in the leaf adaxial domain [155].…”
Section: Hd-zips IIImentioning
confidence: 99%
“…A reciprocal feedback loop controlling the expression of miR396 and its target transcription factors GRF1 and GRF3 has been demonstrated to coordinate transcriptional events required for proper syncytium formation and function Liu et al, 2014b). In addition, a number of miRNAs and their transacting targets were found to be intricately connected through feedback circuits in different growth and developmental contexts, where robust and adaptable transcriptional responses were established (Xie et al, 2003;Gutierrez et al, 2009;Wu et al, 2009;Marin et al, 2010;Yant et al, 2010;Merelo et al, 2016). Our data suggest that the miR858/MYB83 regulatory circuit may involve MYB12, a confirmed target of miR858, whose transcript abundance was positively regulated by MYB83.…”
Section: Discussionmentioning
confidence: 99%
“…At the heart of this complex network lie class III HD-ZIP transcription factors, such as PHABULOSA, PHAVOLUTA and REVOLUTA, and the GARP family transcription factors KANADI 1-4 (KAN1-4), which determine adaxial and abaxial identities, respectively Kerstetter et al, 2001;McConnell et al, 2001;Emery et al, 2003). In addition, class II HD-ZIP proteins and the AS1/AS2 complex determine adaxial identity (Husbands et al, 2015;Merelo et al, 2016), whereas the auxin response factors ARF2, ARF3 (also known as ETTIN) and ARF4 contribute to abaxial identity (Pekker et al, 2005;Guan et al, 2017). The expression patterns of the adaxial and abaxial determinants resolve into complementary domains as a result of different regulatory mechanisms.…”
Section: Defining Adaxial/abaxial Leaf Polaritymentioning
confidence: 99%
“…For instance, KAN1 directly represses AS2 (Wu et al, 2008) and, in turn, the AS1-AS2 complex represses the abaxial factors MIR166 and ARF3 (Husbands et al, 2015). In parrallel, class III HD-ZIP genes are repressed by miR165/166, and the genes coding for these miRNAs are repressed by a class II-class III HD-ZIP protein complex (Merelo et al, 2016). Finally, auxin also plays a role in establishing polarity: its depletion from the adaxial domain, which results from auxin flow from the young leaf primordium to the meristem, is proposed to establish a transient low auxin domain that contributes to leaf polarity (Qi et al, 2014).…”
Section: Defining Adaxial/abaxial Leaf Polaritymentioning
confidence: 99%